The impact of assistive technology on burden and psychological well‐being in informal caregivers of people with dementia (ATTILA Study). Issue 1 (7th October 2020) - Davies, Anna; Brini, Stefano; Hirani, Shashivadan; Gathercole, Rebecca; Forsyth, Kirsty; Henderson, Catherine; Bradley, Rosie; Davies, Lucy; Dunk, Barbara; Harper, Emma; Lam, Natalie; Pank, Lynn; et al.
Abstract: Introduction: Assistive technology and telecare (ATT) may alleviate psychological burden in informal caregivers of people with dementia. This study assessed the impact of ATT on informal caregivers' burden and psychological well‐being. Methods: Individuals with dementia and their informal caregivers were recruited to a randomized‐controlled trial assessing effectiveness of ATT. Caregivers were allocated to two groups according to their cared‐for person's randomization to a full or basic package of ATT and were assessed on caregiver burden, state anxiety, and depression. Caregivers' data from three assessments over 6 months of the trial were analyzed. Results: No significant between‐ or within‐group differences at any time point on caregivers' burden, anxiety, and depression levels were found. Discussion: Full ATT for people with dementia did not impact caregivers' psychological outcomes compared to basic ATT. The length of follow up was restricted to 6 months.